Trends in monitoring of Australia’s threatened birds (1990–2020): much improved but still inadequate - Verdon, Simon J.; Davis, Robert A.; Tulloch, Ayesha; Legge, Sarah M.; Watson, David M.; Woinarski, John C.Z.; Baker, G. Barry; Driessen, Joris; Geyle, Hayley M.; Possingham, Hugh; Garnett, Stephen T. (Emu, 2024)
Monitoring is vital to conservation, enabling conservation scientists to detect population declines, identify threats and measure the effectiveness of interventions. However, not all threatened taxa are monitored, monitoring quality is variable, and the various components of monitoring are likely to differ in their rates of improvement over time. We assessed the presence of monitoring and monitoring quality, using a range of metrics, for all Australia’s threatened bird taxa from 1990 to 2020 (four assessments spanning 30 years). We used our assessments to understand decadal trends in the number of taxa monitored; monitoring quality; and the groups that conduct monitoring. The monitoring of Australia’s threatened birds has increased substantially since 1990, from 19% of taxa to 75% in 2020. Monitoring quality has also improved, with 24.1% of taxa assessed overall as ‘Good’ or ‘Very Good’ in 2020 (up from 4.8% in 1990). However, by 2020, most monitoring programmes still scored poorly for Data availability/reporting, Management linkage, Demographic data and Training/succession planning. In 2020, private individuals and governments accounted for 59% of monitoring contributions, with the greatest number of taxa monitored by private individuals (79 of 166 taxa assessed). Despite improvements in monitoring since 1990, only a minority of taxa had high-quality monitoring in the most recent assessment period. Monitoring is a powerful tool in conservation, justifying investment in improving how it is conducted. We draw on our results and examples of high-quality monitoring programmes to develop a set of priority actions to improve monitoring of Australia’s threatened birds. Although monitoring of Australia’s threatened birds has improved greatly over the last 30 years, most-threatened bird taxa still have inadequate monitoring and systemic changes are required to improve monitoring quality on the scale required. We recommend priority actions to improve monitoring including funding reforms, targeted improvements of poor performing monitoring components and actions to boost some of the current strengths in monitoring programmes. Private individuals conduct monitoring for more taxa than any other group, so boosting the quality of their monitoring is especially important.